2012
DOI: 10.1182/blood-2011-09-380535
|View full text |Cite
|
Sign up to set email alerts
|

A new mouse model mimicking thrombotic thrombocytopenic purpura: correction of symptoms by recombinant human ADAMTS13

Abstract: Deficiency of a disintegrin and metalloproteinase with a thrombospondin type 1 motif, member 13 (ADAMTS13), a VWFcleaving protease, is the key factor in the pathogenesis of thrombotic thrombocytopenic purpura (TTP), a life-threatening thrombotic microangiopathy. It is well established that ADAMTS13 deficiency results in elevated plasma levels of ultralarge VWF multimers (ULVWF), which are prone to induce platelet aggregation; however, the actual trigger of TTP development remains uncertain. Here we de-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
111
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(118 citation statements)
references
References 36 publications
6
111
0
1
Order By: Relevance
“…30 rADAMTS13 also prevented TTP development in a ADAMTS13 knockout mouse model. 31 These promising experimental data strongly suggest that rADAMTS13 administration could become a valuable therapeutic option in TTP. In line with this statement, a phase I clinical trial is underway to evaluate the safety and pharmacokinetics of rADAMTS13 in children and young adults with congenital TTP (BAX930; https:// clinicaltrials.gov/ct2/show/NCT02216084?termϭADAMTS13ϩ baxter&rankϭ1).…”
Section: Forthcoming Targeted Therapiesmentioning
confidence: 98%
“…30 rADAMTS13 also prevented TTP development in a ADAMTS13 knockout mouse model. 31 These promising experimental data strongly suggest that rADAMTS13 administration could become a valuable therapeutic option in TTP. In line with this statement, a phase I clinical trial is underway to evaluate the safety and pharmacokinetics of rADAMTS13 in children and young adults with congenital TTP (BAX930; https:// clinicaltrials.gov/ct2/show/NCT02216084?termϭADAMTS13ϩ baxter&rankϭ1).…”
Section: Forthcoming Targeted Therapiesmentioning
confidence: 98%
“…15 Briefly, we injected mice through their tail veins with VWF (5 mg/kg), VWF (5 mg/kg) plus HDL (2 mg), or saline and drew blood into 3.8% citrate from jugular veins before injection and 3 and 6 hours after injection. Both purified VWF and HDL (Sigma-Aldrich) were from human plasma.…”
Section: Thrombotic Microangiopathy In Adamts13 Knockout Micementioning
confidence: 99%
“…15 We injected 3 groups of ADAMTS13-deficient mice intravenously with purified human VWF (5 mg/kg), VWF (5 mg/kg) plus HDL (2 mg), or saline, respectively, and monitored their platelet counts. In mice injected with VWF only, the platelet counts decreased by more than 30% and 40% at 3 and 6 hours, respectively, whereas in the group injected with VWF plus HDL, platelet counts decreased only slightly (5% and 17%, respectively).…”
Section: Hdl Dampens Vwf-induced Thrombocytopenia In Micementioning
confidence: 99%
“…Antoine et al., showed the normalization of the ADAMTS13 activity in two brothers with congenital TTP when their plasma was mixed with rADAMTS13 obtained from transfected HEK293 cells 25. A preclinical model using ADAMTS13 knockout mice infused with high dose of recombinant human VWF to trigger the disease showed that prophylactic and therapeutic use of rADAMTS13 improved the hematological and pathologic parameters of TTP 26. A phase 1, multicenter, open label, dose‐escalation study involving 15 patients with cTTP between the ages of 12 to 65, with ADAMTS13 activity <6% showed that ADAMTS13 was well tolerated at the three doses tested (5, 20, or 40 U/kg).…”
Section: Recombinant Adamts13 (Radamts13 Bax930)mentioning
confidence: 99%